Elevated Equilibrium Geotherm in Stable Continental Shield: Evidence From Integrated Structural, Hydrological, and Electromagnetic Studies on Nonvolcanic Hot Springs in the Eastern Ghats Belt, India. Issue 2 (7th February 2020) - Maitra, Asmita; Singh, Anand; Keesari, Tirumalesh; Sharma, S.P.; Gupta, Saibal
Abstract: Nonvolcanic hot springs occur within Neoproterozoic granulites of the tectonically stable Eastern Ghats Belt in the Indian shield. Penetrative granulite facies planar structural fabrics in the northern Eastern Ghats Belt are reoriented within an E‐W striking, northerly dipping ductile shear zone that is subsequently dissected by WNW‐ESE trending, subvertical pseudotachylite‐bearing faults and fractures. Tube and dug wells in the area yield both thermal (~60 °C) and nonthermal (~28 °C) water. Chemical analyses reveal that the thermal water is richer in Na +, K +, and Cl −, with lower bicarbonate content. Stable isotope analyses (δ 2 H and δ 18 O) of the thermal and nonthermal waters both plot on the Global Meteoric Water Line; however, tritium and 14 C ages indicate that the nonthermal water is relatively modern, while the thermal waters are older. This suggests that both waters come from distinct reservoirs. Very low frequency electromagnetic studies show that water circulates through the WNW‐ESE trending fracture systems but also exists in isolated pockets within the crystalline country rock. Heat production studies reveal that some host rocks have exceptionally high heat‐producing element concentrations, primarily as thorium within the minerals monazite and thorite. Meteoric waters entrapped for longer times near these heat‐producing element‐rich pockets undergo radiogenic heating, and are shielded from the nonthermal groundwater circulating within the fracture system. The high heat‐producing element distribution in the crust resulting from Neoproterozoic geological events has, thus, elevated the present‐day equilibrium geotherm in the Eastern Ghats Belt, forming sources for shallow‐level, nonvolcanic hot springs within a tectonically inactive terrane. Key Points: Nonvolcanic hot springs occur within part of the Indian continental shield that is characterized by lithologies with high heat production Hot spring and cold groundwater have distinct chemistry, isotopic composition, and ages indicating derivation from different reservoirs Hot water was entrapped near shallow radiogenic sources, indicating an elevated equilibrium geotherm in part of the Indian shield